The role of intermolecular interactions in polyaniline/polyamide-6, 6 pressure-sensitive blends studied by DFT and 1H NMR. (December 2016) - Lopes, Eluise S.; Domingos, Eloílson; Neves, Rodrigo S.; Romão, Wanderson; de Souza, Kátia R.; Valaski, R.; Archanjo, Braulio S.; Souza, Fernando G.; Silva, Alexander M.; Kuznetsov, Alexei; Araujo, Joyce R.
Graphical abstract: Highlights: Pressure sensitivity of 25% MPa −1 was achieved by blending PAni with PA-6, 6 at weight ratio of 11:1. H-bonding between PAni and PA-6, 6 may provide desirable miscibility level in the two amorphous phases. Free energy of mixing in the PA-6, 6/PAni polymer blend, calculated by DFT, is −5.3 kcal mol −1 . Abstract: The aim of this work was to understand the electrical-mechanical response of polyaniline-thermoplastic blends measured under dynamic conditions and to evaluate the effectiveness of this conducting blend as a pressure sensor. The studied composite materials were based on conducting blends composed of polyaniline, as the conducting phase, dispersed into an insulating thermoplastic polymer, polyamide-6, 6. The compression sensitivity (conductivity changes response) of these materials was investigated. The range of polyaniline content in the studied blends was from 50 to 92 wt.%, as estimated from melting enthalpies of temperature-modulated differential scanning calorimetry measurements. PA-6, 6/PAni blend with 92 wt.% PAni showed the highest electrical conductivity (6 × 10 −5  S cm −1 ) due to the presence of positively charged nitrogen atoms (N + ) evidenced by XPS, as well as the highest compression sensitivity (25% MPa −1 ), attributed to the interconnected conducting network formed in PAni phase, as disclosed by SEM images. The first-principles calculations based on the density functional theory (DFT) were used to describe the interactions between NHCO and HNphenyl segments of the PA-6, 6 and PAni chains, respectively. 1 H Nuclear Magnetic Resonance spectra showed good agreement with the theoretical model through the observation of chemical shifts related to the chemical interaction between H from amine-N of PAni and carbonyl groups of PA-6, 6.